Macroalgal Morphogenesis Induced by Waterborne Compounds and Bacteria in Coastal Seawater - Grueneberg, Jan (PLoS One, 2016)
Axenic gametes of the marine green macroalga Ulva mutabilis Føyn (Ria Formosa, locus typicus) exhibit abnormal development into slow-growing callus-like colonies with aberrant cell walls. Under laboratory conditions, it was previously demonstrated that all defects in growth and thallus development can be completely abolished when axenic gametes are inoculated with a combination of two specific bacterial strains originally identified as Roseobacter sp. strain MS2 and Cytophaga sp. strain MS6. These bacteria release diffusible morphogenetic compounds (= morphogens), which act similar to cytokinin and auxin. To investigate the ecological relevance of the waterborne bacterial morphogens, seawater samples were collected in the Ria Formosa lagoon (Algarve, Southern Portugal) at 20 sampling sites and tidal pools to assess their morphogenetic effects on the axenic gametes of U. mutabilis. Specifically the survey revealed that sterile-filtered seawater samples can completely recover growth and morphogenesis of U. mutabilis under axenic conditions. Morphogenetic activities of free-living and epiphytic bacteria isolated from the locally very abundant Ulva species (i.e., U. rigida) were screened using a multiwell-based testing system. The most represented genera isolated from U. rigida were Alteromonas, Pseudoalteromonas and Sulfitobacter followed by Psychrobacter and Polaribacter. Several naturally occurring bacterial species could emulate MS2 activity (= induction of cell divisions) regardless of taxonomic affiliation, whereas the MS6 activity (= induction of cell differentiation and cell wall formation) was species-specific and is probably a feature of difficult-to-culture bacteria. Interestingly, isolated bacteroidetes such as Algoriphagus sp. and Polaribacter sp. could individually trigger complete Ulva morphogenesis and thus provide a novel mode of action for bacterial-induced algal development. This study also highlights that the accumulation of algal growth factors in a shallow water body separated from the open ocean by barrier islands might have strong implications to, for example, the wide usage of natural coastal seawater in algal (land based) aquacultures of Ulva.